Early Interactions between the Hellenistic and Greco-Roman World and the Chinese: The Ancient Afro-Eurasian Routes in Medicine and the Transmission of Disease - Ioannis Solos (Wolters Kluwer Health/LWW, 2021)
This paper discusses the historical exchanges, communications, and circumstances that initially enabled the opening of trade routes between China and the Hellenistic and Greco-Roman world. In addition, it explains how ancient Greeks first became aware of China, and the original premise of trading silk for horses. Historical Chinese texts are analyzed to identify references to the Hellenistic and Greco-Roman world in an attempt to elucidate the extent of official interactions between the two cultures. Historical and archaeological sources confirm that trade existed for millennia before Western Europeans traveled to China during the Age of Exploration. The thesis describes how silk and disease traveled from east to west and explains the historical conditions that allowed the exchange of ideas, practices, beliefs, and culture.